An Analysis of the Legal and Ethical Implications of Online Disinformation in the Philippines - Kenya Silvia Magbanua (Pusat Studi Pembangunan dan Pemberdayaan, 2022)
Online disinformation has become a significant problem in the Philippines, particularly during election periods. This paper examines the legal and ethical implications of online disinformation and presents case studies that illustrate the potential impact of false information on public opinion and democratic processes. The results show that while legal frameworks exist to address online disinformation, enforcement remains a challenge, and there is a need for responsible online behavior and effective regulation to combat the spread of false information. The ethical implications of online disinformation emphasize the importance of media literacy and responsible reporting, as well as the need for accountability among those who engage in the spread of false information. The case studies demonstrate the potential harm caused by online disinformation and the impact it can have on democratic processes. By addressing these issues, we can work towards a more informed and democratic society in which the spread of false information is minimized..